2021
DOI: 10.1111/jocn.15610
|View full text |Cite
|
Sign up to set email alerts
|

Comfort during the bed bath—A randomised crossover trial on the effect of washing without water versus water and soap in nursing students

Abstract: Aims and objectives To compare the washing without water method with the water and soap method regarding comfort perceptions of the bed bath. Background Bathing affects nurses’ and care recipients’ comfort. Bedridden care recipients can be bathed in bed with water and soap or with washing without water products. Little is known about the differences between these two bed bath methods regarding comfort perceptions among care recipients and nurses. Design Crossover randomised laboratory‐controlled trial, conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
0
8
0
1
Order By: Relevance
“…Thus, nurses may wipe more due to potential perceptions that disposable wipes require more effort to remove dirt. Previous studies have also reported that some care recipients perceive that the use of cotton towels with water and soap more effectively removes dirt and makes them feel “really” cleaner than disposable wipes [ 7 , 29 , 44 ]. Therefore, we inferred that the nurses in this study had a similar perception, which was evident in their practice (i.e., NW).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, nurses may wipe more due to potential perceptions that disposable wipes require more effort to remove dirt. Previous studies have also reported that some care recipients perceive that the use of cotton towels with water and soap more effectively removes dirt and makes them feel “really” cleaner than disposable wipes [ 7 , 29 , 44 ]. Therefore, we inferred that the nurses in this study had a similar perception, which was evident in their practice (i.e., NW).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, two systematic reviews have shown that disposable wipes are no less effective than cotton wipes in preventing skin lesions and removing bacteria in older adults [ 13 , 26 ]. Furthermore, disposable wipes have been shown to be a valuable alternative to cotton wipes in terms of comfort of the care recipients [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The length of the washout period depends on the type of treatment; however, 1-2 weeks for single inoculations is suggested (Origasa, 2016). Previous studies on massage and nursing care have also indicated a 1-week washout period (Edwards et al, 2018;Groven et al, 2021;Miyoshi, 2019). The influence of the "carry-over effect" is expected to be eliminated during this period.…”
Section: Methodsmentioning
confidence: 99%
“…Maintaining physical cleanliness, grooming, and protecting the skin are basic human needs (Henderson, 1966). Hygiene care, including bathing, showering, partial bathing, and bed bathing, are part of the nursing care provided to patients who cannot meet these needs on their own (Groven et al, 2021). The aging population and increasing number of chronic diseases in today's society are creating increasing demand for high-quality fundamental care (Feo & Kitson, 2016).…”
mentioning
confidence: 99%
“…Conventional research on nurses' perceptions of hygiene care has mainly explored their satisfaction during hygiene care, time required, financial costs, and their physical comfort using quantitative indices (Groven et al, 2021; Larson et al, 2004; Matsumura & Fukai, 2018; Schoonhoven et al, 2015). Recently, a systematic review was conducted with the aim of qualitatively integrating nurses' and patients' perceptions and experiences in fundamental care, including hygiene care (Pentecost et al, 2019).…”
mentioning
confidence: 99%